Synthesis and Characterization Magnetic Activated Carbon Derived from Coconut Shell for Pb(II) and Cd(II) Adsorption from Wastewater - Sri Rachmania Juliastuti; Amanizar Aji Gumilang (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2025)
Activated carbon derived from coconut shell is a low cost adsorbent for heavy-metal removal. However, recovery of spent carbon from treated water remains challenging. This study developed a magnetically separable activated carbon magnetite composite (M-CSAC) and evaluated its adsorption toward Pb(II) and Cd(II). Coconut shell activated carbon (CSAC) was produced by Na₂CO₃ chemical activation and modified by mechanochemical incorporation of Fe3O4 through ball milling. SEM–EDX confirmed morphology refinement and successful Fe loading (11 wt.%), while increased surface oxygen indicated Fe–O-rich domains. N₂ adsorption–desorption showed that the specific surface area decreased from 356.04 m2/g to 319.35 m2/g. In contrast, total pore volume increased from 0.256 cm3/g to 0.3166 cm3/g and the average pore diameter widened from 2.88 nm to 3.97 nm, consistent with mesopore development. XRD reflections at 2θ = 30.24°, 35.40°, 43.18°, 57.00°, and 62.50° matched magnetite (Fe3O4). Lattice-parameter fitting (a = 8.3837 Å) supported phase stability without detectable γ-Fe2O3. In batch tests (C0 = 50 mg L⁻¹, V = 100 ml, m = 0.5 g), M-CSAC achieved removals of 99.58% for Pb(II) and 96.44% for Cd(II), with Qe values of 9.958 mg/g and 9.644 mg/g, respectively. Overall, M-CSAC combines high adsorption efficiency with practical magnetic separability for water